Screening for Congenital Heart Disease: Sonographic Features and Techniques for Prenatal Detection. (July 2016) - Scott, Ted; Jones, Judy; Swan, Hans
Compared with the assessment of most fetal anatomic structures, the assessment of the fetal heart during routine obstetric screening represents a diagnostic challenge for sonographers and interpreting physicians. This is due to a number of factors: the structural complexity of the heart, the rate at which it moves, the position of the fetus relative to the transducer, and variations in assessment protocols used by sonographers and physicians. The fetal heart is a relatively small and complex structure, as seen in an early second-trimester sonogram. In some forms of congenital heart disease, the abnormality may be detectable within only a relatively small fraction of the heart volume. Congenital heart disease represents a range of structural defects, a number of which have specific sonographic features that can be identified during routine assessment. Many approaches have been proposed to improve the assessment of the fetal heart, including specific still images, color Doppler, 3D imaging techniques, and cineloops.